Efek Mediasi Kredibilitas Selective Exposure dan Algorithmic Personalization terhadap Online Political Engagement Pemuda: Kasus Isu #IndonesiaGelap - Hermawan, Eko Satriya; Asfar, Muhammad; Wicaksana, I Gede Wahyu (Universitas Negeri Surabaya, 2025)
Social media affords both deliberate selective exposure and algorithmic curation. This study examines which pathway better explains youth online political engagement around #IndonesiaGelap issue and whether perceived information credibility mediates these effects. Using PLS-Structural Equation Modelling based on the survey evidence, we find that engagement is driven chiefly by self- selected exposure. Meanwhile, the algorithmic personalization shows only a modest direct association, functioning mainly as a facilitator of visibility rather than a mobilizer. On the other side, credibility operates as a complementary mediator that amplifies the effect of selective exposure on engagement, while contributing little to the transmission of algorithmic effects. These results indicate that online political issue engagement is not simply an algorithmic by-product but arises from intentional information seeking coupled with credible content. Theoretically, the study sharpens the distinction between algorithmic curation and user agency and specifies credibility as a boundary mechanism that conditions especially when exposure translate into engagement. Findings also recommend communication strategies that foreground credible sources, increase information curation, and build media literacy to support deliberate, informed participation.